Potensi dan Tantangan Kerjasama Energi Indonesia-Rusia Pasca Bergabungnya Indonesia Sebagai Anggota BRICS - Wicaksa, Arif; Jamaan, Ahmad; Nizmi, Yusnarida Eka; Hidayati, Umunnisa; Yulia, Rahmi; Purwasandi, Purwasandi (UIN ALAUDDIN MAKASSAR, 2025)
This paper discusses the potential and dynamics of energy cooperation between Indonesia and Russia following Indonesia’s accession as a full member of BRICS in early 2025. In the context of geopolitical tensions, sanctions against Russia, and Indonesia’s urgent domestic energy needs, the Indonesia-Russia energy partnership is viewed as a rational and strategic move. The study employs a liberalist approach, the theory of complex interdependence, and the Two-Level Games framework to analyze how Indonesia conducts its economic diplomacy with Russia. This research is based on a qualitative method utilizing literature review and secondary data. The findings reveal that Indonesia has succeeded in increasing oil imports from Russia without violating international sanctions, while still maintaining constructive relations with Western countries. Nevertheless, Indonesia continues to face challenges, particularly in relation to its national energy transition and the consistency of its foreign policy amid ongoing geopolitical dynamics. Therefore, the Indonesia–Russia energy cooperation should be directed not only at meeting short-term demands but also as part of a long-term, sustainable energy and diplomatic strategy.